Research on the Impact of Free Cash Flow on Corporate Financing Constraints - TianHao Li; HaoJie Liao; YaoChen Wen (Journal of Frontier in Economic and Management Research, 2025)
Free cash flow and financing constraints can exert significant influences on the operational development of enterprises. Based on the pecking order theory and using data from A-share listed companies in China, this paper employs fixed-effects models and moderation effect models to examine the relationship and mechanisms between enterprises' free cash flow generation capacity and their financing constraints.The study found that: (1) Free cash flow can alleviate corporate financing constraints. (2) Corporate performance plays a positive moderating role in the impact of free cash flow on financing constraints. (3) The impact of free cash flow on financing constraints is weaker in state-owned enterprises compared to non-state-owned enterprises. The findings of this paper imply that free cash flow can have a significant impact on corporate financing activities. Therefore, enterprises should pay more attention to their cash flow indicators, signaling their operational stability and risk management capabilities to the outside world, thereby reducing the level of financing constraints faced by the enterprise.